Want to be a real hero ?: uma análise sistêmico-funcional de anúncios em revistas em quadrinhos de super-heróis - Silva, Jordão Joanes Dantas da (2011)
Although North American super-heroes such as Spider-Man and Captain America are originally associated with comic books, it has been very common to see them in other mass media, such as films, video games, cartoons and advertising. With regard to advertisements, which are closely related to a society in which consuming has been defining the human behaviour, these heroic characters are remarkably used in the offering of products and services. Considering that, with a focus on seven advertisements from the comic book The Amazing Spider-Man, this thesis aims at identifying the recurrent advertising strategies, pointing out the verbal and visual choices used in their realizations and discussing possible implications of the advertisements for the delineation of a consuming society. The data analysis follows Systemic-Functional Linguistics (HALLIDAY, 1978), with attention to the transitivity system (HALLIDAY; MATTHIESSEN, 2004) and the representational metafunction (KRESS; van LEEUWEN, 2006). Following this theoretical framework, as well as discussions about consumer society, advertising and super-heroes, it is still created a systemic network with sociosemantic options (HALLIDAY, 2003d; van LEEUWEN, 2005) which are crucial for the identification of advertising strategies and their related linguistic realizations. The findings express three main groups of strategies: Desire for Power, Product/Service Presentation and Necessity. Concerning linguistic aspects, there is a preference for material processes, with the super-heroes (in visual structures) and the addressee (in verbal clauses) mainly represented in the role of Actors. Giving prominence to the system Desire for Power, the advertisements present the product/service as a mediator between the real world of the advertisement addressee and the fictional world of the comic book super-heroes.